Religion and Rationality - mehdi dashti (حکمت و فلسفه, 2012)
A lot has been said about religion and rationality and the possible conflict between them. Since the Renaissance, the West has claimed that they are involved in a constant conflict, the loser of which is religion and the winner is rationality whose era has begun. The present article is an attempt to demonstrate that there is no conflict but absolute harmony between true religion and true rationality. However, if one or both of them are untrue, then conflict emerges. This applies to the conflict between the distorted Christianity and untrue rationality. On the contrary, there is no conflict between the true faith of Islam and the God-given rationality which are both sent to guide mankind to the right path. The Holy Quran and collections of correct narrations both underline the fact that there is complete harmony between religion and rationality, and that religion is based on rationality which is itself the means of understanding religion and attaining obedience, happiness and salvation.